BUILDING ASSESSMENT SKILLS IN FUTURE TEACHERS - Boymirzayev Farhodjon Rahmatjon o’g’li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article examines the issue of developing student assessment skills in future teachers. Assessment in education is considered not only as a control tool, but also as a strategic factor that stimulates student development. During the study, a diagnostic questionnaire, training sessions, observation and final tests were used with the participation of students studying in higher pedagogical educational institutions of Uzbekistan. According to the results, it was found that the sessions conducted based on interactive methods significantly developed students' assessment competencies. The authors substantiated the effectiveness of modern methods such as rubrics, self assessment, and reflection in the assessment process and made suggestions for their introduction into the teacher training process.